Early Weightbearing Versus Nonweightbearing After Operative Treatment of an Ankle Fracture: A Multicenter, Noninferiority, Randomized Controlled Trial. Issue 10 (August 2021) - Park, Jae Yong; Kim, Bom Soo; Kim, Yu Mi; Cho, Jae Ho; Choi, Young Rak; Kim, Hyong Nyun
Background: Acute ankle fractures can occur during sports activities, and unstable ankle fractures are commonly treated operatively. However, controversy exists about the optimal time to allow weightbearing. Hypothesis: Early weightbearing after the stable fixation of an ankle fracture is not inferior to nonweightbearing in terms of ankle function assessed at 12 months after injury. Study design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 258 patients were assessed for eligibility. Of these patients, 194 were randomly allocated to either the early weightbearing group (95 patients who were allowed weightbearing at 2 weeks postoperatively) or the nonweightbearing group (99 patients who were not allowed weightbearing until 6 weeks postoperatively). The primary outcome measure was the mean difference in the Olerud-Molander ankle score (OMAS) between the groups, assessed at the 12-month follow-up examination. The secondary outcome measures were the time to return to preinjury activities and patients' subjective satisfaction. Complications such as hardware loosening or failure, fracture displacement, and nonunion were evaluated. Results: The mean difference in the OMAS for the early weightbearing group compared with the nonweightbearing group was 1.6 (95% CI, –1.9 to 5.0) in the intention-to-treat analysis. The lower limit of the 95% CI (–1.9) exceeded the noninferiority margin of –8, indicating that early weightbearing was not inferior to nonweightbearing. The difference in the proportion of patients who were satisfied or very satisfied with their treatment was not statistically significant (84.3% vs 76.2%; P = .19); however, the time taken to return to preinjury activities was shorter with early weightbearing than with nonweightbearing (9.1 ± 3.0 vs 11.0 ± 3.0 weeks; P < .001). No cases of nonunion were observed in either group. Conclusion: Early weightbearing after the operative treatment of an unstable ankle fracture was not inferior to nonweightbearing in terms of OMAS assessed at 12 months after injury. The patients' subjective satisfaction was similar between the groups, although the time taken to return to preinjury activities was shorter in the early weightbearing group. Registration: NCT02029170 (ClinicalTrials.gov identifier).